ALOKASI PENGELUARAN KONSUMSI RUMAH TANGGA MIGRAN DENGAN RUMAH TANGGA NON MIGRAN (Studi Kasus Desa Besuki Kecamatan Besuki Kabupaten Tulungagung) - Fitrada, Muhammad Verda (Jurnal Ilmiah Mahasiswa FEB, 2018)
Given the large number of Indonesian Workers (TKI) and also the potential remittance that goes to this Besuki district. In addition, many researches or research finds that in general remittance of TKI is used for consumption purposes so it needs to be studied how the allocation of household consumption expenditure in Besuki Village. With some predetermined variables, this study aims to: (1) To find out how the allocation of household consumption expenditure of migrants with non migrant households in Besuki Village. (2) To know whether there is a difference in the allocation of household consumption expenditure of migrants to non-migrant households in Besuki Village. (3) To determine the effect of family income, the number of family members, the number of school children and the level of education on household consumption expenditure in Besuki Village. The place and time of this research is the household in Besuki Village of Tulungagung Regency in May 2017. The analysis method used is multiple linear regression. The results showed that income, the number of family members, the number of school children, and the level of education had a positive and significant impact on the household consumption expenditure of migrants. In non-migrant households, the number of schoolchildren had negative and insignificant impact on household consumption expenditure.Keywords: Household consumption, income, number of family members, number of school children, education level.